GLOBALISASI, MODERNISASI, DAN PAUGERAN DI KESULTANAN YOGYAKARTA - Sigit Surahman (KAREBA : Jurnal Ilmu Komunikasi, 2020)
The awarding of the title "Mangkubumi" to Gusti Kanjeng Ratu Pembayun, contextualises the successor to the throne. In the Islamic kingdom of Yogyakarta has never been led by a queen. This seems to be the step of the Sri Sultan HBX to change the position of the Yogyakarta Sultanate. The demands of globalization, especially the emancipation of equal rights of men and women, are the reason. The openness of the leader's mind determines the progress of the Yogyakarta Sultanate. Three information on globalization: 1) slowly leaving modernity. 2) moving towards new conditions. 3) Demonstrate the dynamics of development (Steger, 2008: 8). Cultural globalization refers to intensification and expansion. Associated with culture, globalization is a symbolic construction, and articulation, some opinions suggest that cultural practice lies in contemporary globalization (Steger, 2008: 69). Paugeran did not become a reason for rejecting the appearance of the Queen in the height of modern power. Development dynamics and the creative economy make life balance in the welfare of society. The social and cultural environment in Yogyakarta changes with the needs and realization of life. Like the spatial layout of the city, the tourism sector and culture in Yogyakarta. In this era of globalization it provides a space for gender equality and male domination is a past for women in the Yogyakarta Sultanate.